2011
DOI: 10.1002/ijc.26138
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic repression of regulator of G‐protein signaling 2 promotes androgen‐independent prostate cancer cell growth

Abstract: G-protein coupled receptor (GPCR)-stimulated androgen-independent activation of androgen receptor (AR) contributes to acquisition of a hormone-refractory phenotype by prostate cancer. We previously reported that regulator of G-protein signaling (RGS) 2, an inhibitor of GPCRs, inhibits androgen-independent AR activation.1 Here, we show reduced RGS2 protein expression in human prostate cancer specimens compared to adjacent normal or hyperplastic tissue. Methylation-specific PCR analysis and bisulfite sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 50 publications
9
45
0
Order By: Relevance
“…Immunohistochemistry was performed by using a polyclonal anti-RGS2 C-terminal peptide antibody as previously described. 18 The negative control used nonimmune rabbit IgG as the primary antibody. The intensity of RGS2 protein staining was determined as an average optical density by Image-Pro Plus in 5 randomly chosen airways for each sample.…”
Section: Selection Of Subjects and Methacholine Airway Challengesupporting
confidence: 39%
See 2 more Smart Citations
“…Immunohistochemistry was performed by using a polyclonal anti-RGS2 C-terminal peptide antibody as previously described. 18 The negative control used nonimmune rabbit IgG as the primary antibody. The intensity of RGS2 protein staining was determined as an average optical density by Image-Pro Plus in 5 randomly chosen airways for each sample.…”
Section: Selection Of Subjects and Methacholine Airway Challengesupporting
confidence: 39%
“…Total RNA was extracted from monocytes, and procedures for quantitative real-time PCR of the RGS2 gene were described previously. 18,23 Immunohistochemistry analysis of human lung tissues Archived formalin-fixed, paraffin-embedded lung tissue blocks of subjects with asthma (n 5 3) and healthy controls (n 5 5) were from Dr Reynold A. Panettieri. Immunohistochemistry was performed by using a polyclonal anti-RGS2 C-terminal peptide antibody as previously described.…”
Section: Selection Of Subjects and Methacholine Airway Challengementioning
confidence: 49%
See 1 more Smart Citation
“…Previous gene expression analyses in several myeloid cell lines showed induction of RGS2 expression during granulocytic differentiation [22]. Further, it has been reported that epigenetic repression of RGS2 promotes prostate cancer cell growth [23]. Our microarray and QPCR data showed RGS2 is suppressed in leukemic cells and up-regulated after treatment of 5-aza-dC suggesting that targeting Wnt-signaling may be valuable in treating leukemia.…”
Section: Discussionsupporting
confidence: 43%
“…RGS2 mRNA expression is lower in breast cancerous tissues than in normal tissues and research suggests that its overexpression exerts an inhibitory effect of breast cancer cell growth [18]. RGS2 is specifically downregulated in androgen-independent prostate cancer cells (AIPCC) and research found that RGS2 functioned as a growth suppressor for AIPCC [85,86]. An RGS2 decrease may contribute to chronic inflammation leading to metaplasia and may eventually lead to carcinogenicity in the skin keratinocytes [87].…”
supporting
confidence: 39%